2021
DOI: 10.3390/ijms22094941
|View full text |Cite
|
Sign up to set email alerts
|

G4 Matters—The Influence of G-Quadruplex Structural Elements on the Antiproliferative Properties of G-Rich Oligonucleotides

Abstract: G-quadruplexes (G4s) are non-canonical structures formed by guanine-rich sequences of DNA or RNA that have attracted increased attention as anticancer agents. This systematic study aimed to investigate the anticancer potential of five G4-forming, sequence-related DNA molecules in terms of their thermodynamic and structural properties, biostability and cellular uptake. The antiproliferative studies revealed that less thermodynamically stable G4s with three G-tetrads in the core and longer loops are more predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 50 publications
(68 reference statements)
6
24
0
Order By: Relevance
“…Comparing all the hairpin gapmers with the control gapmer, only in one case ( ON16 ), the β‐actin silencing level was worse. Increasing the efficiency of gapmers may be the result of greater stability of these oligonucleotides in the cell or such structured gapmers might better pass through cellular compartments [25] . Presumably, decreased effectiveness of ON16 in comparison to other hairpin forming gapmers is due to the highest thermodynamic stability of this structure among the group and thus lower ability to unfold process prior to interactions with mRNA target.…”
Section: Resultsmentioning
confidence: 99%
“…Comparing all the hairpin gapmers with the control gapmer, only in one case ( ON16 ), the β‐actin silencing level was worse. Increasing the efficiency of gapmers may be the result of greater stability of these oligonucleotides in the cell or such structured gapmers might better pass through cellular compartments [25] . Presumably, decreased effectiveness of ON16 in comparison to other hairpin forming gapmers is due to the highest thermodynamic stability of this structure among the group and thus lower ability to unfold process prior to interactions with mRNA target.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, at 50 µM and after 72 h of treatment, INT-B resulted in a reduction of 90% of cell viability (Figure 6B-D). Recently, some authors have highlighted the influence of G-quadruplex structural elements on the antiproliferative properties of certain G-rich oligonucleotides [40]. In our case, it is interesting to note that in both cell lines, the most significant antiproliferative results were related to INT-B, the unique ODN characterized by an intact dimeric G-quadruplex structure, suggesting that both its typical folding in dimeric form and the presence of all thymidines in the sequence are pivotal features for this biological activity.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…Recently, the attention of many research groups has focused on the antiproliferative potential of guanosine-rich oligonucleotides. These molecules are usually G-quadruplexes that are able to interact specifically with proteins involved in the cell cycle, which could restrain cell proliferation [43][44][45]. What is more, it has also been demonstrated that some modified TBA variants with decreased anticoagulant properties are characterized by favorable antiproliferative activity [21,31].…”
Section: Antiproliferative Properties Of Modified Thrombin Binding Aptamer Variantsmentioning
confidence: 99%